A phase I/IIa study of the mRNA-based cancer immunotherapy CV9201 in patients with stage IIIB/IV non-small cell lung cancer - Sebastian, Martin; Thomas, Michael (Cancer immunology immunotherapy, 2019)
CV9201 is an RNActive®-based cancer immunotherapy encoding five non-small cell lung cancer-antigens: New York esophageal squamous cell carcinoma-1, melanoma antigen family C1/C2, survivin, and trophoblast glycoprotein. In a phase I/IIa dose-escalation trial, 46 patients with locally advanced (n = 7) or metastatic (n = 39) NSCLC and at least stable disease after first-line treatment received five intradermal CV9201 injections (400-1600 µg of mRNA). The primary objective of the trial was to assess safety. Secondary objectives included assessment of antibody and ex vivo T cell responses against the five antigens, and changes in immune cell populations. All CV9201 dose levels were well-tolerated and the recommended dose for phase IIa was 1600 µg. Most AEs were mild-to-moderate injection site reactions and flu-like symptoms. Three (7%) patients had grade 3 related AEs. No related grade 4/5 or related serious AEs occurred. In phase IIa, antigen-specific immune responses against ≥ 1 antigen were detected in 63% of evaluable patients after treatment. The frequency of activated IgD+CD38hi B cells increased > twofold in 18/30 (60%) evaluable patients. 9/29 (31%) evaluable patients in phase IIa had stable disease and 20/29 (69%) had progressive disease. Median progression-free and overall survival were 5.0 months (95% CI 1.8-6.3) and 10.8 months (8.1-16.7) from first administration, respectively. Two- and 3-year survival rates were 26.7% and 20.7%, respectively. CV9201 was well-tolerated and immune responses could be detected after treatment supporting further clinical investigation.
Gesehen am 07.10.2019